Opposing Effects of Plant Invasion on the Stability of Aboveground and Belowground Net Primary Productivity in an Alpine Grassland - Qiu‐Jie Ren; Kai‐Hui Li; Heng‐Fang Wang; Yan‐Yan Liu; Yan‐Ming Gong (Ecology and Evolution)
ABSTRACT Plant invasion significantly disrupts plant community structure and ecosystem functioning, especially the stability of net primary productivity (NPP). However, evidence remains scarce regarding how invasion affects NPP stability at both community and ecosystem levels, particularly whether these effects are consistent between aboveground and belowground systems. Here, we investigated the responses of the stability of both aboveground and belowground NPP (ANPP and BNPP) to the invasion of the parasitic plant Pedicularis kansuensis, based on a two‐year manipulative experiment in an alpine grassland in northwest China. Invasion decreased ANPP resistance while increasing its recovery and conversely increased BNPP resistance but decreased its recovery. Notably, the asymmetric responses of ANPP and BNPP to invasion underscored the complexity of grassland ecosystems and highlighted the critical role of belowground processes in maintaining ecosystem recovery. Species asynchrony and richness were key factors for ANPP stability, whereas BNPP stability was more directly influenced by invasive species, contributing more significantly to overall NPP stability. Our findings provide crucial evidence that the stability of aboveground and belowground components responds asymmetrically to invasion, emphasizing the need for future comprehensive assessments of both dimensions in ecosystem studies. The insights gained underline the importance of belowground stability for sustaining ecosystem recovery and offer guidance for ecological management and conservation strategies.